NOVEL APPROACH TO DESIGN OF LIGHTWEIGHT AND RELIABLE COMPOSITE PRIMARY AIRCRAFT STRUCTURES - M. Ch. Zichenkov; I. O. Kondakov; A. N. Shanygin (Научный вестник МГТУ ГА, 2017)
The experience of construction of composite primary aircraft structures has approved that the weight decrease for composite aggregates of aircraft in comparison with metallic analogues cannot be obtained within the frames of conventional structures based on stiffened laminated composite skin. One of the main reasons is the low level of stress-strain characteris- tics of current polymer resins, which does not allow to realize high strength characteristics of carbon fibers in laminated composite packages. This consequence does not allow to use stiffened composite skin as a universal structure element, un- like metallic stiffened skin that sustains all main mechanical loads, including impact, loads from pressurizing and also sus- tains environmental factors. Hence, creation of lightweight and reliable composite primary structure elements of airframe, the novel types of structure layouts, allowing to realize high potential of current composite materials to the maximal extent, should be developed. In order to provide the development of such layots the novel approach is required, as the conventional stage-by-stage approach is based on a number of sufficient assumptions, most of which are correct only for the structures made of metallic alloys, but not correct as applied to the structures made of composite materials. The impossibility of the application of a stage-by-stage approach together with a significant increase of number of design parameters (in comparison with metallic structures), leads to the radical increase of labor input of the design task of composite structures.The novel approach to design of composite airframes, allowing to significantly decrease the extremely high labor input of the design process for composite structures is presented in this study. The approach presumes simultaneous solu- tions of design tasks on different levels of detailing of composite aircraft structure within the frames of the one integral design stage. The application of the novel approach allowed to obtain a number of lightweight solutions for the structure of cylindrical fuselage section of civil aircraft and for the hermetic cabin of the "Flying wing" aircraft.